Epidemiological Profile of HIV/AIDS of the 7th Health Regional of the State of Paraná, in the Period from 2009 to 2019 (Research, Society and Development, 2022)
Objective: To realize an epidemiological analysis of the population diagnosed with HIV/AIDS in the 7th Health Regional Office in the state of Paraná (7th RS-PR), Brazil, between the years 2009 and 2019. Methodology: Observational epidemiological study of the descriptive-retrospective type, with a quantitative approach, conducted from secondary data of AIDS cases notification from the Department of Chronic Conditions Diseases and Sexually Transmitted Infections made available by the Ministry of Health between 2009 and 2019. A descriptive statistical analysis was performed using the Kruskal-Wallis test. Results: The Kruskal-Wallis statistical test showed by means of the Chi-Square (X2) that for all variables evaluated the p-values observed were